Influence of Fluorescent Tag on the Motility Properties of Kinesin-1 in Single-Molecule Assays - Norris, Stephen R. (Biophys J, 2015)
Molecular motors such as kinesin and dynein use the energy derived from ATP hydrolysis to walk processively along microtubule tracks and transport various cargoes inside the cell. Recent advancements in fluorescent protein (FP) research enable motors to be fluorescently labeled such that single molecules can be visualized inside cells in multiple colors. The performance of these fluorescent tags can vary depending on their spectral properties and a natural tendency for oligomerization. Here we present a survey of different fluorescent tags fused to kinesin-1 and studied by single-molecule motility assays of mammalian cell lysates. We tested eight different FP tags and found that seven of them display sufficient fluorescence intensity and photostability to visualize motility events. Although none of the FP tags interfere with the enzymatic properties of the motor, four of the tags (EGFP, monomeric EGFP, tagRFPt, and mApple) cause aberrantly long motor run lengths. This behavior is unlikely to be due to electrostatic interactions and is probably caused by tag-dependent oligomerization events that appear to be facilitated by fusion to the dimeric kinesin-1. We also compared the single-molecule performance of various fluorescent SNAP and HALO ligands. We found that although both green and red SNAP ligands provide sufficient fluorescent signal, only the tetramethyl rhodamine (TMR) HALO ligand provides sufficient signal for detection in these assays. This study will serve as a valuable reference for choosing fluorescent labels for single-molecule motility assays.